The Adaptive Performance Model of Marines: The Role of Job Demands and Crafting Strategy - Dwi Warih Untari; Fendy Suhariadi; Andreas Budihardjo (Psympathic : Jurnal Ilmiah Psikologi, 2022)
The success of the Marine Corps organization depends on the ability of its personnel to respond positively and overcome environmental challenges, acquire the new required skills, take official orders assiduously, and exhibit the adaptive performance from assigned tasks. Therefore, this study aims to analyze the adaptive performance model suitable for Marine Corps personnel by using job demands and crafting strategy as predictor and mediator variables, respectively. A quantitative method was used with cross-sectional and purposive sampling techniques. The model was tested using a sample of 230 Marine Intermediate Officers. The goodness of fit of the adaptive performance model is quite positive, with RMR = .05, CFI = .926, and TLI= .908. The results of the Structural Equation Model (SEM) analysis with AMOS 22 showed that: 1) the adaptive performance model offered for Marine Intermediate Officers is quite fit. 2) Job demands have a strong direct effect on adaptive performance. 3) Job crafting acts as a partial mediator between work demands and adaptive performance.